2005
DOI: 10.1590/s1413-70542005000100019
|View full text |Cite
|
Sign up to set email alerts
|

Características morfogênicas e estruturais do capim-elefante 'napier' adubado e irrigado

Abstract: RESUMOObjetivou-se avaliar a dinâmica do aparecimento, do alongamento e da senescência de folhas do capim-elefante 'Napier' após pastejo de uniformização. O trabalho consistiu de dois experimentos, para o estudo de quatro tratamentos de adubação (T1: 100 kg de N e 80 kg de K, T2: 200 kg de N e 160 kg de K, T3: 300 kg de N e 240 kg de K e T4: 400 kg de N e 320 kg de K), sendo um irrigado e outro sem irrigação, segundo o delineamento de blocos ao acaso com três repetições. As plantas da área irrigada atingiram u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 17 publications
1
3
1
4
Order By: Relevance
“…However, although there was no significant statistical difference, the values found are of increased LAI as increased irrigation to values close to 100% of replenishment, declining soon after, being consistent with those found for the first cut of forage sorghum. On the other hand, the results obtained of increase of the LAI in different depths of water in relation to the non-irrigated treatment are similar to those obtained by Andrade et al (2005). The authors, in study realized analyzing the growth of grass-elephant "NAPIER" fertilized and irrigated, observed increased leaf area index in the irrigated plot, with an average of 8.27 compared to the average of the non-irrigated treatment 7, 76.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…However, although there was no significant statistical difference, the values found are of increased LAI as increased irrigation to values close to 100% of replenishment, declining soon after, being consistent with those found for the first cut of forage sorghum. On the other hand, the results obtained of increase of the LAI in different depths of water in relation to the non-irrigated treatment are similar to those obtained by Andrade et al (2005). The authors, in study realized analyzing the growth of grass-elephant "NAPIER" fertilized and irrigated, observed increased leaf area index in the irrigated plot, with an average of 8.27 compared to the average of the non-irrigated treatment 7, 76.…”
Section: Resultssupporting
confidence: 82%
“…According to Andrade et al (2005), the evaluation of growth of forage species makes it possible to identify the characteristics of plants, associated with the adaptations to adversities caused by stress, as well as their potential for optimal growth conditions. The results are consistent with those obtained by Fagundes et al (2006), who observed reduction in grass-braquiária IAF in the period with lower availability of water.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Vilela et al (2005), using 200 kg ha -1 of nitrogen in Coastcross-1 pastures, observed much higher rates, 2.6 cm -1 .day -1 , for the average of three seasons. Those values are higher than what we observed in this study, possibly due to the high nitrogen fertilizer doses they used, which increase leaf elongation rate (OLIVEIRA et al, 2007;MARTUSCELLO et al, 2005;ANDRADE et al, 2005). Different letters in the columns indicate difference according to the Tukey test, at 5% significance (P < 0.05).…”
Section: Resultscontrasting
confidence: 73%
“…Andrade et al (2005) registraram o intervalo médio de aparecimento de folhas consecutivas em (dia -1 folhas) para os perfilhos basais de capim-elefante em 7,1 (dia -1 folhas).…”
Section: Resultsunclassified